Exploring the restorative benefits of work in smart working structures on vacations in small villages - Maffei, Luigi; Ciervo, Antonio; Marzocchi, Raffaella; Masullo, Massimiliano (Frontiers in Psychology, 2023)
Introduction Processes of redefinition of work, already in place in the pre-pandemic era, with the advent of COVID-19, have become widely required. A “model of work” that uses new technologies and the development of existing ones to improve workers’ performance and satisfaction has emerged. Smart working has changed how people work and, as a result, spaces must also change to support them. The use of prefabricated movable buildings (PMB) could represent an opportunity to create smart (and co-) working spaces in a regenerative contest. Small villages with historical, architectural, and naturalistic elements and slow-life features are potential platforms where vacation and work could merge easily. This paper aims to establish if working in movable offices, like the PMBs, which provide a high level of visual and acoustics interaction with the surroundings, and which is positioned in small villages’ squares, can affect workers’ sense of restoration and working performance. Methods In a laboratory setting, in the SENS i-Lab, a videowall and a 3D spatial audio system were used to compare, in terms of restorativeness and self-reported cognitive performance, the effects of a high-rise building context of a City Business District (CBD), i.e. the control scenario, and of two typical squares of small Italian villages with historic buildings, without (HIS) and with water elements (HIS-W). Results The findings of the experimental sessions showed that when working in close contact (visual and auditory) with historical or water elements, where life flows slowly, workers perceived a higher sense of restoration while job performance was unchanged. Discussion Implementing smart working policies in small villages that encourage the use of energy-efficient prefabricated movable buildings and that offer a high level of visual and acoustic interaction with the surrounding environment may represent a promising strategy to foster the development of the local economy and contrast the depopulation of small villages, improving the worker well-being and the reducing the impact of their activities of the environment.